On Robert Flaherty and the documentary form - Chris Hainstock; Denis Forman; Nick Broomfield; Stella Bruzzi; Mark Reynard; Paul Henley; George Stoney (2014)
Sir Denis Forman, Nick Broomfield, Stella Bruzzi, Michael Reynard, Paul Henley and George Stoney discuss Robert Flaherty and the Documentary FormOriginally interviewed as part of the film 'A Boatload of Wild Irishman' Distributed by Icarus Films (AKA 'The Wandering Irishman')A BOATLOAD OF WILD IRISHMEN includes testimony from Flaherty himself as well as contributions from amongst others, Richard Leacock - cameraman on 'Louisiana Story' (1948) and father of the contemporary hand-held documentary style, Martha Flaherty - Flaherty's Inuit granddaughter, George Stoney - documentary filmmaker and professor at New York University, Sean Crosson - film scholar at the Huston School of Film, Jay Ruby - anthropologist and film scholar at Temple University, and Deirdre Ni Chonghaile - musician and folklorist from Arainn, as well as telling interviews with the people whose parents and grandparents Flaherty put onto the cinema screens of the world: Inuit, Samoans and, of obvious personal interest to the Irish filmmakers, the 'wild men' of Aran.Originally interviewed as part of the film 'The Wandering Irishman' Distributed by Icarus Films